Between invisibility and homonormativity: LGBT+ referents for spanish adolescents. Issue 4 (2nd October 2022) - Francisco Amat, Andrea; González-de-Garay, Beatriz; Moliner Miravet, Lidón
Abstract: Studies show the importance of non-cis-heteronormative referents for LGBT+. The object of this paper is to explore LGBT+ referents for teenagers on the basis of the results of the "Survey on Adolescence and Sexual Diversity, " which was distributed to Spanish high school students in the fourth grade of compulsory secondary education The sample was composed of 128 students aged 15–18. About 56.2% identified as girls, 43.8% identified as boys; none identified as non-binary or trans. The results of the quantitative analysis of the survey data highlight the invisibility of non-heteronormative identities and the role of the media as the main purveyor of these identities. Suggestions are offered for the transformation of communicative spaces to embrace diversity and inclusivity.